Effect of nanoparticles concentration on electromagnetic-assisted oil recovery using ZnO nanofluids - Adil, M. (Public Library of Science, 2020)
Utilization of metal-oxide nanoparticles (NPs) in enhanced oil recovery (EOR) has generated substantial recent research interest in this area. Among these NPs, zinc oxide nanoparticles (ZnO-NPs) have demonstrated promising results in improving oil recovery due to their prominent thermal properties. These nanoparticles can also be polarized by electromagnetic (EM) field, which offers a unique Nano-EOR approach called EM-assisted Nano-EOR. However, the impact of NPs concentrations on oil recovery mechanism under EM field has not been well established. For this purpose, ZnO nanofluids (ZnO-NFs) of two different particle sizes (55.7 and 117.1 nm) were formed by dispersing NPs between 0.01 wt. to 0.1 wt. in a basefluid of sodium dodecylbenzenesulfonate (SDBS) and NaCl to study their effect on oil recovery mechanism under the electromagnetic field. This mechanism involved parameters, including mobility ratio, interfacial tension (IFT) and wettability. The displacement tests were conducted in water-wet sandpacks at 95oC, by employing crude oil from Tapis. Three tertiary recovery scenarios have been performed, including (i) SDBS surfactant flooding as a reference, (ii) ZnO-NFs flooding, and (iii) EM-assisted ZnO-NFs flooding. Compare with incremental oil recovery from surfactant flooding (2.1 original oil in place/ OOIP), nanofluid flooding reaches up to 10.2 of OOIP at optimal 0.1 wt. ZnO (55.7 nm). Meanwhile, EM-assisted nanofluid flooding at 0.1 wt. ZnO provides a maximum oil recovery of 10.39 and 13.08 of OOIP under EM frequency of 18.8 and 167 MHz, respectively. By assessing the IFT/contact angle and mobility ratio, the optimal NPs concentration to achieve a favorable ER effect and interfacial disturbance is determined, correlated to smaller hydrodynamic-sized nanoparticles that cause strong electrostatic repulsion between particles. Â© 2020 Adil et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.